Belgium : Technical Note on Stress Testing the Banking and Insurance Sectors. (IMF Staff Country Reports; Country Report ;, 2013)
The Belgium Financial Sector Assessment Program (FSAP) stress testing exercise examines a financial sector that remains in a state of transformation. Domestic economic challenges remain sources of continued uncertainty as the banking sector consolidates and reduces funding risks. Insurers face challenges from adverse economic and business conditions. Solvency and funding shocks under different macroeconomic scenarios were assessed. Both banking and insurance tests underscore the importance of sovereign risk for financial stability. The implementation of stress tests needs to be closely aligned with the resolution and recovery planning.